HIC1 interacts with FOXP3 multi protein complex: Novel pleiotropic mechanisms to regulate human regulatory T cell differentiation and function - Andrabi SBA; Batkulwar K; Bhosale SD; Moulder R; Khan MH; Buchacher T; Khan MM; Arnkil I; Rasool O; Marson A; Kalim UU; Lahesmaa R (Netherlands, 2025)
Transcriptional repressor, hypermethylated in cancer 1 (HIC1) participates in a range of important biological processes, such as tumor repression, immune suppression, embryonic development and epigenetic gene regulation. Further to these, we previously demonstrated that HIC1 provides a significant contribution to the function and development of regulatory T (Treg) cells. However, the mechanism by which it regulates these processes was not apparent. To address this question, we used affinity-purification mass spectrometry to characterize the HIC1 interactome in human Treg cells. Altogether 61 high-confidence interactors were identified, including IKZF3, which is a key transcription factor in the development of Treg cells. The biological processes associated with these interacting proteins include protein transport, mRNA processing, non-coding (ncRNA) transcription and RNA metabolism. The results revealed that HIC1 is part of a FOXP3-RUNX1-CBFB protein complex that regulates Treg signature genes thus improving our understanding of HIC1 function during early Treg cell differentiation.